Genetic diversity of Rubus glaucus Benth in the municipality of Pamplona (northeastern Colombia) (BISTUA Revista de la Facultad de Ciencias Básicas, 2022)
In Colombia, the area of R. glaucus Benth cultivation has increased since 2000, as it has organoleptic and economic characteristics of great attractiveness for national and international trade. The improvement of the supply of this product in the country, in a context of climate change, will depend on the implementation of new propagation techniques by farmers and the use of superior genotypes, with high diversity and free of pathogens. In this work, 7 polymorphic Simple Sequence Repeats (SSR) were selected to characterize the genetic fingerprint diversity in 92 individuals of R. glaucus in 23 farms of Pamplona (northeastern Andes of Colombia). DNA extraction was performed using the Invisorb® Spin plant kit. Microsatellites G01, R47a, R123a, R167h, R228a and R285a were amplified by PCR and revealed in 12% polyacrylamide gel. The DICE similarity index, analysis of molecular variation (AMOVA) and multiple correspondence analysis (MCA) reported that the blackberry population evaluated shows moderate to high genetic diversity (67% due to variation of individuals within farms and 33% between farms). The average values of polymorphic information content PIC = 0.302 and expected heterogeneity He = 0.388 indicate that the SSRs are suitable for future research on this species. This work contributes new data to the knowledge of genetic diversity in cultivars of R. glaucus in Colombia, and a set of microsatellites that provide useful information to implement better strategies for plant propagation of blackberry with the support of farmers in the region.